Educational Games in Education of Communication Culture of Pre-School Children - Boyborieva Saodat (Universitas Muhammadiyah Sidoarjo, 2022)
The article deals with some issues of teaching children to think independently through didactic games in speech development classes in preschool education, and expresses theoretical views.